2015
DOI: 10.1073/pnas.1416723112
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of pheromone processing reveals main olfactory system-mediated social behaviors in mice

Abstract: Most mammals have two major olfactory subsystems: the main olfactory system (MOS) and vomeronasal system (VNS). It is now widely accepted that the range of pheromones that control social behaviors are processed by both the VNS and the MOS. However, the functional contributions of each subsystem in social behavior remain unclear. To genetically dissociate the MOS and VNS functions, we established two conditional knockout mouse lines that led to either loss-of-function in the entire MOS or in the dorsal MOS. Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 59 publications
(84 reference statements)
4
84
3
Order By: Relevance
“…The main olfactory system detects mainly volatile odorants and MHC molecules (Spehr et al 2006) via the main olfactory epithelium which projects to the main olfactory bulb and the anterior olfactory nucleus. The vomeronasal system is important for the detection of nonvolatile pheromones and major histocompatibility complex (MHC) molecules (Leinders-Zufall et al 2004) by activation of the vomeronasal epithelium which projects to the accessory olfactory bulb (Matsuo et al 2015). The two subsystems provide complementary information when the animal is confronted by another animal.…”
Section: Resultsmentioning
confidence: 99%
“…The main olfactory system detects mainly volatile odorants and MHC molecules (Spehr et al 2006) via the main olfactory epithelium which projects to the main olfactory bulb and the anterior olfactory nucleus. The vomeronasal system is important for the detection of nonvolatile pheromones and major histocompatibility complex (MHC) molecules (Leinders-Zufall et al 2004) by activation of the vomeronasal epithelium which projects to the accessory olfactory bulb (Matsuo et al 2015). The two subsystems provide complementary information when the animal is confronted by another animal.…”
Section: Resultsmentioning
confidence: 99%
“…The involvement of the main olfactory system (MOS) in vomeronasal phenotypes is evident from studies with MOS loss-of-function mouse models (Mandiyan et al 2005;Wang et al 2006;Matsuo et al 2015). We therefore could not rule out the possibility that the defect of maturation and survival of VSNs might be due to the indirect effect of the global ATF5 deficiency, since at least MOS in ATF5 −/− mice also have abnormal phenotypes (Wang et al 2012;Umemura et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Actually, the size of the olfactory bulb is reduced in ATF5 −/− mice compared with that in the wild-type (Umemura et al 2015), and olfactory sensory neurons (OSNs) in the ATF5 −/− MOE remain immature and frequently undergo apoptosis (Wang et al 2012;Umemura et al 2015). In addition, ATF5 −/− mice display reduced inter-male aggression (Umemura et al 2015), and this behavior is regulated by the vomeronasal sensory system (Stowers et al 2002;Chamero et al 2011;Prince et al 2013), but also by the main olfactory sensory system (Mandiyan et al 2005;Wang et al 2006;Matsuo et al 2015). In this study, we investigated the effect of deficiency of ATF5 in VSNs using ATF5 −/− mice.…”
Section: Introductionmentioning
confidence: 99%
“…Unconditional disruption of genes that encode signal transduction proteins that are required for activating olfactory neurons resulted in the impairment of several social behaviors [6163]. More recently, Mastuo et al selectively deleted the dorsal part of the MOB and found that the manipulation reduced aggression towards males and also ultrasonic vocalization towards females, whereas copulatory behavior remained relatively unchanged [64]. However, these mutant mice lacking the dorsal MOB showed mostly normal investigation towards a conspecific and the activity in the AOB was unchanged.…”
Section: Social Investigation Activates the Accessory Olfactory Systemmentioning
confidence: 99%